Exploring Consumer Perceptions of the Negative Effects of Red Meat Consumption on the Environment: A Green Demarketing Opportunity - Stassi, Francesco (2020)
The present study was initiated to determine the extent of the participants’ awareness of the negative outcomes of red meat consumption and their readiness to reduce such consumption for ecological reasons due to demarketing practices that they were exposed to. The study analysed the awareness of consumers concerning the environmental impact of meat production and consumption, examined their readiness to reduce red meat consumption due to environmental reasons, analysed the changes in the consumption of meat because of environmental reasons, and analysed the possible influence of demarketing practices on the consumers’ awareness, readiness to change consumption, and changes in consumption. The sample was selected using a quota sampling method, resulting in 107 participants, aged between 18 and 32. The questionnaire designed for and implemented in this study consisted of a total of 14 questions, divided into four categories. The first segment collected demographic information; the second segment investigated the participants’ awareness of the adverse effects of red meat consumption. The third part of the instrument tried to obtain information about how deeply rooted the consumption of red meat is in the eating habits of the respondent; and, consequently, how difficult it is to change certain habitual food choices. The fourth segment of the questionnaire examined the participants’ attitudes to what can be called communication campaigning aimed at discouraging red meat consumption. Overall, the findings indicated that there is low awareness of the ads against excessive red meat consumption among people in England and Italy. Moreover, the data analysis showed that environmental reasons do not present a markable motivational factor for reducing red meat consumption. Finally, the demarketing strategies were not significant predictors of the participants’ intention to reduce red meat consumption, not their actual limiting or eliminating red meat in their weekly eating patterns. Nonetheless, the findings also suggested that demarketing efforts do have an impact, and they might be utilised in a carefully designed combination with other psychological phenomena and other motivators, to reach the desired goal of limiting the negative impact of excessive farming and consumption of red meat on the environment. The alleys to achieving the goal of a more responsible approach to human lives and the sustainment of the planet for the future generations were discussed in detail. It was recommended that the demarketing messages are framed to ensure a durable behavioural change, such as addressing the root causes of the lack of motivation to reduce red meat consumption and presenting ads and messages in a manner that would speak to the population’s emotions and values, gradually moving towards more explicit messages and systemic responses.